ORGANIZATION OF INDEPENDENT WORK ON THE SUBJECT "MATERIAL DESIGNING" IN THE FIELD OF TECHNOLOGICAL EDUCATION IN THE CREDIT-MODULE SYSTEM - Majidovich, Muxamedov Shavkat (The journal of contemporary issues in business and government, 2021)
The article discusses one of the urgent tasks of the modern education system - bringing education in line with world standards. The ways of introducing a credit-modular system into the education system based on European standards are described. Including the methods used in the training of technology teachers on the credit-modular system in higher education. There is a method of organizing independent work in the field of material designing. The features of the tasks of independent work are taken into account. The types of independent work are also explained. The advantages of using the credit-modular system in higher education are described, recommendations are given, the importance of training future teachers through self-study is revealed.